Rapid isolation of respiring skeletal muscle mitochondria using nitrogen cavitation - Younis, Awais Z.; Lavery, Gareth G.; Christian, Mark; Doig, Craig L. (Frontiers in Physiology, 2023)
Methods of isolating mitochondria commonly utilise mechanical force and shear stress to homogenize tissue followed by purification by multiple rounds of ultracentrifugation. Existing protocols can be time-consuming with some physically impairing integrity of the sensitive mitochondrial double membrane. Here, we describe a method for the recovery of intact, respiring mitochondria from murine skeletal muscle tissue and cell lines using nitrogen cavitation. This protocol results in high-yield, pure and respiring mitochondria without the need for purification gradients or ultracentrifugation. The protocol takes under an hour and requires limited specialised equipment. Our methodology is successful in extracting mitochondria of both cell extracts and skeletal muscle tissue. This represents an improved yield in comparison to many of the existing methods. Western blotting and electron microscopy demonstrate the enrichment of mitochondria with their ultrastructure well-preserved and an absence of contamination from cytoplasmic or nuclear fractions. Using respirometry analysis we show that mitochondria extracted from murine skeletal muscle cell lines (C2C12) and tibialis anterior tissue have an appropriate respiratory control ratio. These measures are indicative of healthy coupled mitochondria. Our method successfully demonstrates the rapid isolation of functional mitochondria and will benefit researchers studying mitochondrial bioenergetics as well as providing greater throughput and application for time-sensitive assays.